A protocol study of participatory action research: integrated care pathway for pregnant women with heart disease in Indonesia - Suryani Yuliyanti; Adi Utarini; Laksono Trisnantoro (BMC, 2020)
Abstract Background Heart diseases are increasingly identified as an important indirect cause of maternal mortality in several cities in Indonesia. The management of pregnancy with heart diseases requires a multidisciplinary approach, and interprofessional collaboration practice (IPCP) is critical to improving the quality of patient care. To enable the effective implementation of IPCP, integrated care pathways (ICPs) are needed to define the roles and responsibilities of the health professionals involved. This study aims to examine the obstacles and enabling factors of IPCP, to develop and use ICPs in the implementation of IPCP in health care services for pregnant women with heart diseases. Methods A participatory action study consisting of four stages (diagnostic, planning, implementation, and evaluation) will take approximately 2 years after consensus of ICPs are made. The primary data collection process will employ consensus, observations, focus group discussions, and in-depth interviews throughout the four stages, while secondary data from referral documents and medical records will be collected mainly during the diagnostic and evaluation stages. The findings are being analysed and will then be used to develop an ICPs through consensus building at the planning stage to be applied in the implementation stage. Finally, the implementation outcome, including acceptability, adoption, appropriateness, and feasibility of IPCP, will be assessed in the evaluation stage. All qualitative data will be analysed thematically by two coders using NVIVO 12 software. Discussion This research aims to assess the needs of IPCP, develop and use the ICPs in the implementation of IPCP in health care services for pregnant women with heart diseases. Findings from this study will be used for health service planning and policy making to strengthen practice of IPCP during the referral process. As a result, pregnant women with heart disease will have better access to high-quality services at every health care facility to reduce maternal mortality. Trial registration Retrospectively registered in the ISRCTN registry with study ID ISRCTN82300061 on Feb 6, 2019.